Performance evaluation of a novel disk-type motor using ultrasonic levitation: Modeling and experimental validation - Shi, Minghui; Gao, Ming; Chen, Shujie; Zhang, Shaolin; Miao, Xinming (Precision engineering, 2024)
Experimental measurements and theoretical analyses of a novel non-contact ultrasonic motor driven by near-field acoustic levitation are presented, in which the proposed motor is comprised of a Langevin transducer, stator disk and rotor disk. In exciting of Langevin transducer, the air layer between the stator disk and rotor disk is squeezed by high frequency vibration, forming acoustic levitation force and acoustic radiation torque which is caused by the introduction of artificial asymmetry. The experimental results show that the rotational speed increases with driving voltage and is sensitive to exciting frequency. To predict the running performance of the motor, a theoretical model with the consideration of motion of rotor disk is introduced, which is based on Navier-Stokes equations. The comparison of theoretical and experimental results shows that the developed theoretical mode is effective and the proposed motor are hopeful to be used in precision machinery. [Display omitted] •A novel disk-type motor using ultrasonic levitation is proposed.•A theoretical model based on Navier-Stokes equations is built to reveal the operating mechanism of the NCUM.•The harmonic analysis and streaming analysis are conducted by using the finite element analysis software.•Experimental investigations are conducted using a specially designed experimental device.